Social Linguistics and Literacies: Ideology in Discourses. Social Linguistics and Literacies: Ideology in Discourses. - Constance C. Gerger (Ilha do Desterro, 2008)
Many people in "literate" societies, when asked to define literacy, almost always do so in terms of reading
and writing abilities. This narrow interpretation of literacy, an
offspring of reductionist psychology, has reigned supreme in many academic and educational contexts for decades, greatly shaping literacy theories and classroom practices. Within the past ten years, however, a large body of multidisciplinary
research has begun to undermine the authority of this
perspective by situating literacy in larger social practices. Many people in "literate" societies, when asked to define literacy, almost always do so in terms of reading
and writing abilities. This narrow interpretation of literacy, an
offspring of reductionist psychology, has reigned supreme in many academic and educational contexts for decades, greatly shaping literacy theories and classroom practices. Within the past ten years, however, a large body of multidisciplinary
research has begun to undermine the authority of this
perspective by situating literacy in larger social practices.